Deciphering price dynamics: A bibliometric analysis of research trends in the financial market - Moraes, Alexandra Kelly de; Castro Junior, Luiz Gonzaga de (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Background: The dynamics of financial price behavior have become a central theme in economic literature, especially considering increasing market volatility, technological advancements, and new global interdependencies. Understanding the factors that influence this dynamic is crucial, particularly in a scenario marked by uncertainties and ongoing digital transformations. Purpose: This study aims to investigate the evolution of the scientific literature on financial price dynamics from 1970 to 2024. The focus is on mapping the trajectory of research, identifying its theoretical and social foundations, and outlining the emerging trends that shape the current and future research agenda in the field. Method: A bibliometric approach was adopted, analyzing 3,648 publications extracted from the Scopus and Web of Science databases. The analysis process was divided into three stages: (i) temporal evolution of scientific production, (ii) analysis of the conceptual and social foundation through co-occurrence networks, thematic mapping, and author collaboration, and (iii) identification of emerging trends, with an emphasis on thirteen areas of study. Results: The literature on price dynamics showed consistent growth, with notable peaks during economic crises and technological innovations. The scientific production revealed increasing integration between micro and macroeconomic approaches, with a focus on empirical models. Conclusions: The emerging trends indicate that the integration of advanced technologies and sustainable practices will significantly impact price modeling and investment decision-making. The research also points to new directions, such as considering environmental variables and the need for hybrid and adaptive models to cope with the volatility and complexity of financial markets.